Development of an efficient strategy to improve HPV immunization coverage in Japan. (December 2016) - Yagi, Asami; Ueda, Yutaka; Egawa-Takata, Tomomi; Tanaka, Yusuke; Morimoto, Akiko; Terai, Yoshito; Ohmichi, Masahide; Ichimura, Tomoyuki; Sumi, Toshiyuki; Murata, Hiromi; Okada, Hidetaka; Nakai, Hidekatsu; et al.
Abstract Background In Japan, new HPV immunizations have dropped dramatically after repeated adverse media reports and a June 2013 temporary suspension of the government's recommendation for the vaccine. The aim of the present study was to develop an efficient strategy to improve HPV immunization coverage across Japan. Methods We conducted an internet survey in Japan of mothers of 12–16 year-old girls who were unvaccinated as of May, 2015. The goal was to gather behavioral information from the mothers to develop a strategy for improving Japanese HPV immunization coverage. Results Valid survey answers were obtained from 2060 mothers. The survey found that a hypothetical restart of a governmental recommendation for the vaccine would induce 4.1 % of all the mothers surveyed to be more likely to encourage vaccination of their daughters, without any other preconditions. This initial result would be followed by a moderate spread of vaccinations to these daughters' close friends and acquaintances, hypothetically resulting in a total vaccination rate of 21.0 % of the targeted age-eligible girls. As a second critical step for improving vaccinations, an educational information sheet integrating the concepts of behavioral economics for changing behaviors was found to be significantly effective for persuading mothers with poorer decision-making facilities, who would otherwise prefer to wait to first see the vaccination of other girls of the same age as their daughter. Conclusions Following what we foresee as the inevitable restart of the Japanese government's recommendation for receiving the HPV vaccine, we expect to first see vaccinations occurring in a very small group of girls, the daughters of the most willing mothers, which will be roughly 4 % of those eligible for government paid vaccinations. This will be followed by the spread of vaccinations outward through these girls' circle of friends and acquaintances, and, finally, to the daughters of the most skeptical mothers, those who would await the return of new vaccine safety results from a large group of similarly-aged girls. As a critical step in improving HPV vaccine coverage in Japan, an educational information sheet that integrates the concepts of behavioral economics for changing behaviors can be employed to persuade mothers with poor decision-making facilities.